2000
DOI: 10.1053/joca.1999.0299
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine HCl reduces equine articular cartilage degradation in explant culture

Abstract: Objective To determine whether glucosamine inhibits experimentally induced degradation of equine articular cartilage explants. Methods Articular cartilage was obtained from the antebrachio-carpal and middle joints of horses (2-8 years old) killed for reasons unrelated to lameness. Cartilage discs were harvested from the weight-bearing region of the articular surface and cultured. Media were exchanged daily and the recovered media stored at 4 degrees C. Explants were maintained in basal media 2 days prior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
102
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 35 publications
5
102
0
Order By: Relevance
“…Higher concentrations (2.5 mg/ml or higher) of GLN alone inhibit MMP activity (Fenton et al 2000). Glucosamine also inhibits aggrecanases (enzymes involved in the initiation of proteoglycan degradation) in vitro (Sandy et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations (2.5 mg/ml or higher) of GLN alone inhibit MMP activity (Fenton et al 2000). Glucosamine also inhibits aggrecanases (enzymes involved in the initiation of proteoglycan degradation) in vitro (Sandy et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…12 Other in vitro studies show that incubation of chondral explants in glcN after exposure of the tissue to the proinflammatory cytokine interleukin-1 prevents the increase in PG release and MMP activity. 13 Thus, the hypotheses of the current study were that: during low intensity, intermittent cyclic loading, a high concentration of glcN-CS would upregulate the production of PGs to reduce the extent of matrix damage and cell death following an acute overload; and supplementation of the culture media would limit, or even mitigate, the degeneration effect noted to occur between 14 and 21 days in this model. These would suggest that athletes could take this nutraceutical prophylactically prior to and during intense practice and competition to protect their joint cartilage in case of excessive overload, such as during rupture of a ligament.…”
mentioning
confidence: 93%
“…Several clinical trials have shown the significant symptom-modifying effect of glucosamine in OA (18)(19)(20). In this context, biochemical and pharmacological studies have suggested in vitro that glucosamine possibly exhibit chondroprotective action by inhibiting the degradation and stimulating the synthesis of proteoglycans (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Several short-and long-term clinical trials in osteoarthritis have shown the significant symptom-relieving and structure-modifying effects of glucosamine (18)(19)(20). Importantly, it has been revealed in vitro that glucosamine can inhibit the degradation and stimulate the synthesis of glycosaminoglycans (proteoglycans), thereby possibly exhibiting chondroprotective action (21,22). Moreover, glucosamine has been shown to inhibit the expression of collagen-degrading enzymes (matrix metalloproteinases, MMPs) but augment the expression of type II collagen in chondrocytes in vitro (23,24).…”
Section: Introductionmentioning
confidence: 99%